2010
DOI: 10.1016/j.molcel.2010.07.001
|View full text |Cite
|
Sign up to set email alerts
|

K11-Linked Polyubiquitination in Cell Cycle Control Revealed by a K11 Linkage-Specific Antibody

Abstract: Polyubiquitination is a posttranslational modification where ubiquitin chains containing isopeptide bonds linking one of seven ubiquitin lysines with the C terminus of an adjoining ubiquitin are covalently attached to proteins. While functions of K48- and K63-linked polyubiquitin are understood, the role(s) of noncanonical K11-linked chains is less clear. A crystal structure of K11-linked diubiquitin demonstrates a distinct conformation from K48- or K63-linked diubiquitin. We engineered a K11 linkage-specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
347
0
8

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 341 publications
(365 citation statements)
references
References 31 publications
10
347
0
8
Order By: Relevance
“…55,56 X-ray crystallography indeed revealed that the K11-linked, K48-linked and K63-linked polyubiquitin-chains adopt distinct structures, respectively. 57 Given this, our experimental data can be interpreted that Ubc4 also has the ability to ubiquitinate Slp1, but the chain cannot become targeted for proteasomal proteolysis. On the other hand, a recent study has suggested that multiple monoubiquitination can also become a degradation signal, at least for Cyclin B1.…”
Section: Discussionmentioning
confidence: 76%
“…55,56 X-ray crystallography indeed revealed that the K11-linked, K48-linked and K63-linked polyubiquitin-chains adopt distinct structures, respectively. 57 Given this, our experimental data can be interpreted that Ubc4 also has the ability to ubiquitinate Slp1, but the chain cannot become targeted for proteasomal proteolysis. On the other hand, a recent study has suggested that multiple monoubiquitination can also become a degradation signal, at least for Cyclin B1.…”
Section: Discussionmentioning
confidence: 76%
“…P. falciparum seems to contain a relatively high proportion of K11 linkages, 13.3%. K11 linkages in humans are suspected of playing a key role in mitotic protein degradation (49). In S. cerevisiae, high levels of K11 linkages have been observed and are suspected to be of major importance in ERAD of proteins (50).…”
Section: Discussionmentioning
confidence: 99%
“…UbcH10 is responsible primarily for monoubiquitination (or initiation of polyubiquitination) of APC/C substrates 24,25 , whereas Ube2S catalyses ubiquitin chain elongation (or polyubiquitination) of the monoubiquitinated APC/C substrates [26][27][28] . Co-depletion of UbcH10 and Ube2S abrogates Lys11-linked polyubiquitination of APC/C substrates, stabilizing APC/C substrates and resulting in severe mitotic delay in human cells 27,29 . However, Ube2S may be required for normal mitosis only in a subset of cell types, although it may be important for recovery from the spindle checkpoint in human cells 26,27 .…”
mentioning
confidence: 99%